2021
DOI: 10.22541/au.161217752.23254903/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating animal behaviour into research on multiple environmental stressors: a conceptual framework

Abstract: While a large body of research has focused on the physiological effects of multiple environmental stressors, behavioral effects remain far less studied. However, behavioural plasticity can not only directly drive responses to stressors but can also mediate physiological responses. Here, we provide a conceptual framework incorporating four fundamental tradeoffs explicitly linking animal behaviour to life history-based pathways for energy allocation, shaping the impact of multiple stressors on fitness. We first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 120 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…Currently, our framework does not consider the spatial dimension since the effects of multiple drivers on dispersal are incompletely understood ( Lopez et al, 2021 ). However, a distributed experiment across a range of model organisms has shown that top-down (i.e., predator cues) and bottom-up effects (i.e., resource availability) will modulate dispersal ( Fronhofer et al, 2018 ).…”
Section: Implications For Future Research and Conclusionmentioning
confidence: 99%
“…Currently, our framework does not consider the spatial dimension since the effects of multiple drivers on dispersal are incompletely understood ( Lopez et al, 2021 ). However, a distributed experiment across a range of model organisms has shown that top-down (i.e., predator cues) and bottom-up effects (i.e., resource availability) will modulate dispersal ( Fronhofer et al, 2018 ).…”
Section: Implications For Future Research and Conclusionmentioning
confidence: 99%
“…Time and effort spent on predator detection and avoidance can be critical to survival. However, such activities can also conflict with other important behaviours, such as foraging and mate attraction [13]. Indeed, the energetic demands of antipredator behaviours can be substantial enough to have negative population and ecosystem-level consequences [47].…”
Section: Introductionmentioning
confidence: 99%